2011
DOI: 10.1017/s0007114511006234
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of malnutrition in spinal cord injuries patients: a UK multicentre study

Abstract: Data on the prevalence of malnutrition among patients with spinal cord injuries (SCI) are lacking. The aim of the present study was to assess nutritional risk at admission, and the status of nutritional support in the UK SCI Centres (SCIC); a cross-sectional, multicentre study in four SCIC. A standardised questionnaire was used and distributed to the participating SCIC. After obtaining informed consent, baseline demographic data, nutritional risk score by the 'Malnutrition Universal Screening Tool', BMI and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
4
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 14 publications
2
55
4
4
Order By: Relevance
“…Consuming adequate amounts of nutrition can be challenging for some, particularly in acute injury where malnutrition rates of up to 40% have been reported. 7 In the long term, reduced ability to …”
mentioning
confidence: 99%
“…Consuming adequate amounts of nutrition can be challenging for some, particularly in acute injury where malnutrition rates of up to 40% have been reported. 7 In the long term, reduced ability to …”
mentioning
confidence: 99%
“…This finding is consistent with previous reports that patients with CSCI are prone to malnutrition and hypoproteinemia in the days and weeks immediately following injury. 16,21 Using mean serum proteins levels to assess nutritional health during this early stage of CSCI, this study demonstrated that patients with CSCI who survived or died were at increased risk for hypoproteinemia and malnutrition during the early period following admission. Hypothetically, it is likely that patients who died in this acute period were more likely to have exhibited negative systemic effects related to poor nutrition and secondary cervical damage, which may be more closely related than previously believed.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations revealed that 44.3% of patients with CSCI were at risk for malnutrition or were already malnourished at the time of admission. 16 Furthermore, patients with CSCI with damage high in the cervical column (C1-4) were more commonly malnourished than other patient groups, and nutritional deficiency was most common in patients requiring ventilatory support. 16 Recent research has indicated that pathological damage below the level of injury in patients with SCI may actually contribute to a number of different complications that affect various organ systems to promote malnutrition, implicated in reduced wound healing and overall poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Despite its importance, malnutrition is rarely identified by clinicians working in general hospitals 2 or in SCI centres (SCIC). 3 We reported previously that the provision of dietetic resources in SCIC is suboptimal, 4 and therefore, it is imperative that hospital catering staff in conjunction with ward-based personnel are proficient in optimising menu design, and in adapting menus, that they have the ability to improve the mealtime atmosphere, and are able to deal with individual patient needs as well as offering a balanced menu that meets patients' nutritional requirements.…”
Section: Introductionmentioning
confidence: 99%